Simple computer model for the quantum Zeno effect - Wallace, D (American Inst of Physics, 2001)
Quantum Zeno effect was modeled for the measurement of the position of a one-dimensional particle. The effects of measurement upon dynamics were simulated using two different measurement processes. Different effects were shown by different measurements. In some measurements slowing of evolution resulted, while others accelerated the evolution.